APLIKASI BEHAVIORISME DALAM PEMBELAJARAN ANAK UNTUK MENCIPTAKAN GENERASI BERKARAKTER - Ahmad Syukri Sitorus (Universitas Islam Negeri Sumatera Utara, 2016)
The influence of the environment very large role in shaping the behavior of a person. The character although congenital but contain elements of true character can be changed, that is because the figures are strongly influenced by external factors, namely families, schools, society and the environment. The effort of preparing and shaping experiences that later will be fruitful in the planting concept for someone, stimulation-stimulating education are expected. If a teacher wants to apply the concept in learning to form behaviorisme children character, then a must set objectives and then design and behavioral learning tool to achieve the goal of behavioral. In addition, the teacher must also be able to integrate the character formation strategies in learning activities, among others, example, spontaneous activity, reprimand, conditioning the environment and routine activities.